3(f-4)=0

Simple and best practice solution for 3(f-4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(f-4)=0 equation:



3(f-4)=0
We multiply parentheses
3f-12=0
We move all terms containing f to the left, all other terms to the right
3f=12
f=12/3
f=4

See similar equations:

| 7=q2− –6 | | 8(a+6)=6(a+12) | | y=-2*10^-07*500^2+0.0006*500 | | 8x−2x+–11x+–9x=–14 | | 6(y+4)=5(y+6) | | y=-2^-07*500^2+0.0006*500 | | 12y-10=50 | | -9x=207 | | (3^3x-5)+21=0 | | y=-2E-07*500^2+0.0006*500 | | -4x²+4x+3=0 | | 3^3x-5+21=0 | | 5x-11=4(2x-2) | | 3^(3x-5)+21=0 | | 10x-15+9x+5=180 | | x=3+3/4 | | X^5-2x-3=0 | | 3^2x+5=9^x-2 | | 5x-3=1+8x+13 | | -(d-6)=0 | | 32=20-3h | | x^2(x-1)=4(2x-3) | | 6x-1+4x+11=90 | | b-10/2=-13 | | 3x=8+4x | | x^2(x-1)=4(x-3) | | 31-3b=4 | | 4f-48-18=-2 | | e+11/9=2 | | 39=4b+7 | | i/5+6=11 | | 6-v=4 |

Equations solver categories